2010
DOI: 10.1016/j.ejvs.2010.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Short Leukocyte Telomere Length is Associated with Abdominal Aortic Aneurysm (AAA)

Abstract: Our data show that patients with AAA have shorter leukocyte telomere length compared to controls. This suggests that vascular biological aging may have a role in the pathogenesis of AAA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
35
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 46 publications
2
35
0
Order By: Relevance
“…These data are in agreement with the results of other studies performed in aorta diseases, i.e., particularly in abdominal aorta aneurysms (Atturu et al 2010;Yan et al 2011;Björck et al 2011). However, they are opposite to those of Salonurmi's group study performed in a population affected by ascending aorta aneurysms (Huusko et al 2012).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These data are in agreement with the results of other studies performed in aorta diseases, i.e., particularly in abdominal aorta aneurysms (Atturu et al 2010;Yan et al 2011;Björck et al 2011). However, they are opposite to those of Salonurmi's group study performed in a population affected by ascending aorta aneurysms (Huusko et al 2012).…”
Section: Discussionsupporting
confidence: 83%
“…Consistent with these observations, a series of recent studies demonstrated significant associations between the reduction of telomere leukocyte length and the risk of several CVDs, such as aorta aneurysms. In particular, Atturu and colleagues observed that short leukocyte telomere length is associated with abdominal aortic aneurysm, by examining a European population and evaluating the mean terminal restriction fragment (TRF) length, a marker of telomere length (Atturu et al 2010). Yan and colleagues demonstrated a significant shorter leukocyte telomere length in a Chinese population affected by aortic dissection (Yan et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12] In addition, a significant reduction in telomere content of AAA wall samples compared to normal aorta and in AAA patients than controls has been detected. 12,13 The mechanisms linking blood telomere attrition to CVD have been studied recently, 6 and number of potential explanations have been suggested. 6 First, the strong association between human blood leukocyte and vessel wall telomere content may be determined genetically, and shorter telomeres may predispose to CVD development.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10][11] This assumption is based on the evidence that telomere content (the TTAGGG DNA repeats at the ends of chromosomes) in circulating blood leukocytes accurately reflects the biological age of the vascular wall, as recently demonstrated by Wilson et al 12 Furthermore, a series of recent epidemiological studies have demonstrated association of the reduction of blood telomere length with several CVD, such as AAA. [6][7][8][9][10][11][12] Patients with AAA showed a shorter leukocyte telomere length compared to controls, as verified by Atturu et al 13 In light of this evidence, our studies are aimed at determining whether the mean of blood leukocyte telomere length might be a predictor for S-TAA. 14 histopathological and phenotypic analyses, and exclusion criteria for syndromic and familial forms (e.g., Marfan and Ehler-Danlos syndromes) and autoimmune connective tissue disorders were used.…”
Section: Introductionmentioning
confidence: 99%
“…In a number of observational studies, it has been documented that short telomeres or the genetics regulating telomeres are associated with hypertension, 4 type 2 diabetes 5 and cardiovascular disease manifestations, for example, risk of coronary heart disease, 6,7 stroke 8 and abdominal aortic aneurysm. 9 This could be due to the association with intermediate phenotypes, such as obesity, hypertension or chronic inflammation, or to the influence of a less healthy lifestyle. 10 However, some of the findings have also been contradictory.…”
mentioning
confidence: 99%